2017
DOI: 10.1017/s1092852917000177
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of suicide attempt and clinical characteristics of suicide attempters with obsessive-compulsive disorder: a report from the International College of Obsessive-Compulsive Spectrum Disorders (ICOCS)

Abstract: Our international study found a history of SA prevalence of ~15% in OCD patients, with higher rates of psychiatric and medical comorbidities and previous hospitalizations in patients with a previous SA. Along with potential geographical influences, the presence of the abovementioned features should recommend additional caution in the assessment of suicide risk in OCD patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 43 publications
3
27
0
2
Order By: Relevance
“…Four main findings emerged. First, confirming previous studies conducted in clinical and community settings [1][2][3][4][5][43][44][45][46], individuals with OCD were at significantly increased risk of suicide attempts and death by suicide compared to individuals without OCD, and the risks were more pronounced for female than male OCD sufferers, similar to the results of another Swedish study on OCD and suicide [2]. This was anticipated in relation to suicide attempts, as nonfatal suicidal behavior is known to be more common in females [28,47].…”
Section: Discussionsupporting
confidence: 84%
“…Four main findings emerged. First, confirming previous studies conducted in clinical and community settings [1][2][3][4][5][43][44][45][46], individuals with OCD were at significantly increased risk of suicide attempts and death by suicide compared to individuals without OCD, and the risks were more pronounced for female than male OCD sufferers, similar to the results of another Swedish study on OCD and suicide [2]. This was anticipated in relation to suicide attempts, as nonfatal suicidal behavior is known to be more common in females [28,47].…”
Section: Discussionsupporting
confidence: 84%
“…The observed increase of attempted and completed suicide in prospective studies, especially the one from Fernandez et al 2017, is comparable to the reports from previous crosssectional and retrospective studies: Data from 3711 adult patients with primary OCD that came from several countries indicated that suicidal ideation within the last month was reported by 6.4% (n = 200) of patients with OCD and a lifetime history of suicide attempt was observed in 9.0% (n = 314) (Brakoulias et al 2017). In agreement, patients with a previous suicide attempt had significantly higher rates of comorbid psychiatric disorders (Dell'Osso et al 2017). This data were supported by the studies reviewed by Angelakis et al (2015).…”
Section: Outcome Of Literature Searchsupporting
confidence: 81%
“…44 In a multicenter study, the rate of suicide attempts was 14.6% in OCD patients. 45 We found lifetime suicide attempts to be 17.9% in OCD patients. We also found suicidal thoughts and lifetime suicide attempts to be significantly higher in the OCD group than the controls.…”
Section: Discussionmentioning
confidence: 75%